The perceived impact of artificial intelligence on jobs at a financial services organization in Johannesburg - Zhou, Nyasha (My University, 2022)
This research study investigated the impact of Artificial Intelligence (AI) on jobs at a financial services (FS) organization in Johannesburg. AI has the ability beyond human comprehension for certain human tasks to be done and its advent introduces the potential for job reconfigurations. The research study’s purpose was to explore the perceived impact of AI technologies on jobs at a FS organization in Johannesburg. It aimed to ascertain if AI is impacting jobs negatively at a FS organization in Johannesburg. The research study was conducted using the Task-Technology Fit conceptual framework. The research study was underpinned by a theoretical framework comprised of four pillars where literature was reviewed in the context of the research problem. The qualitative study was conducted using Saunders research onion’s (Mahesh, 2020) interpretivist research philosophy of an inductive nature. Through the use of a case study as a research strategy over a crosssectional time horizon, sixteen (16) semi-structured interviews were conducted online at a FS organization. This data was coded through thematic analysis and was analysed with reference to literature reviewed. From the research analysis, the perceived notion of AI impacting jobs negatively in a FS organization in Johannesburg was disproved as AI was found to impact jobs positively. The research study’s outcome provides recommendations classified into three perspectives that emanated from the study. These recommendations are to aid the FS organization in Johannesburg in mitigating the impact of AI on jobs. The research also recommends job impact mitigating factors to other FS organizations based in Johannesburg and the world at large.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Artificial intelligence; Financial services organization; AI technologies; UCTD; SDG-8: Decent work and economic growth